Strategi meminta dalam wacana kelas di Madrasah Aliyah Alkhairaat Palu - Ali, Ali (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This strategy is aimed at describing the use of ”asking” strategy in the classroom discourse, namely (1) asking strategy by the teacher and its usage to the students, asking strategy used by the students and its usage to the teacher, and (3) asking strategy used by the students and its usage to the students. Based on the data analysis, it is found out that ”asking strategy ” in the classroom is applied using direct and indirect strategy by all participants or students. In general, the teacher applies direct asking strategy to the students by using moof interogatif. Meanwhile, either the teacher or the students applies direct asking strategy by using declarative and interrogative mods.